Calibration of 16 × 16 SOI optical phased arrays via improved SPGD algorithm. (January 2023) - Wang, Zihao; Wu, Beibei; Liao, Jiali; Li, Xifeng; Wang, Chen; Sun, Yanling; Jin, Li; Feng, Junbo; Cao, Changqing
Highlight: We have designed and fabricated a larger scale two-dimensional independently phase-controlled silicon optical phased array (OPA), and we have improved the conventional OPA beam calibration algorithm to ensure that it is applicable to large array OPAs. In the paper, we illustrate the principle and applicable scenarios of the improved algorithm through simulations, and we also demonstrate the effectiveness of the proposed improved algorithm through experiments. Abstract: We report in this paper the design and testing scheme of 16 × 16 optical phased arrays (OPAs) based on the silicon-on-insulator (SOI) platform. We improve the conventional stochastic parallel gradient descent algorithm used to calibrate its output beam, and verify the improved algorithm superiority through simulations and experiments. The experimental results are consistent with the theoretical values of the OPA design, proving the high quality of the chip and the reliability of the algorithm. We assume that this OPA design approach and the algorithm can provide help for the development and application of LiDAR.